Selumetinib - a potential small molecule inhibitor for osteoarthritis treatment - Zheng, Xiaohang; Qiu, Jianxin; Pan, Wenjun; Gong, Yuhang; Zhang, Weikang; Jiang, Ting; Chen, Lihua; Chen, Weifu; Hong, Zhenghua (Frontiers in Pharmacology, 2022)
Objectives: Osteoarthritis (OA) is a common disease that mainly manifests as inflammation and destruction of cartilage and subchondral bone. Recently, necroptosis has been reported to play an important role in the development of OA. Selumetinib displays a contrasting expression pattern to necroptosis-related proteins. The present study aimed to investigate the potential therapeutic effects of selumetinib in OA process. Methods:In vitro experiments, interleukin-1β (IL-1β) was used to induce necroptosis of chondrocytes. We used high-density cell culture, Western Blot and PT-PCR to observe the effect of different concentrations of selumetinib on the extracellular matrix of cartilage. Afterwards, we visualized the effect of selumetinib on osteoclast formation by TRAP staining and F-actin rings. In vivo experiment, we induced experimental osteoarthritis in mice by surgically destabilizing the medial meniscus (DMM) while administering different concentrations of selumetinib intraperitoneally. Results: Selumetinib promoted cartilage matrix synthesis and inhibited matrix decomposition. We found that selumetinib exerted a protective function by inhibiting the activation of RIP1/RIP3/MLKL signaling pathways in chondrocytes. Selumetinib also inhibited the activation of RANKL-induced NF-κB and MAPK signaling pathways in BMMs, thereby interfering with the expression of osteoclast marker genes. In the DMM-induced OA model, a postsurgical injection of selumetinib inhibited cartilage destruction and lessened the formation of TRAP-positive osteoclasts in subchondral bone. Conclusion: Selumetinib can protect chondrocytes by regulating necroptosis to prevent the progression of OA and reduce osteoclast formation. In summary, our findings suggest that selumetinib has potential as a therapeutic agent for OA.